If you are so smart, why aren't you an entrepreneur? Returns to cognitive and social ability ; entrepreneurs versus employees - Joop Hartog; C. Mirjam van Praag; Justin van der Sluis (Institute for the Study of Labor (IZA), 2008)
How valuable are cognitive and social abilities for entrepreneurs' incomes as compared to employees? We answer three questions: (1) To what extent does a composite measure of ability affect an entrepreneur's earnings relative to employees? (2) Do different cognitive abilities (e.g. math ability, language ability) and social ability affect earnings of entrepreneurs and employees differently?, and (3) Does the balance in these measured ability levels affect an individual's earnings? Our individual fixed-effects estimates of the differential returns to ability for spells in entrepreneurship versus wage employment account for selectivity into entrepreneurial positions as determined by fixed individual characteristics. General ability has a stronger impact on entrepreneurial incomes than on wages. Entrepreneurs and employees benefit from different sets of specific abilities: Language and clerical abilities have a stronger impact on wages, whereas mathematical, social and technical ability affect entrepreneurial incomes more strongly. The balance in the various kinds of ability also generates a higher income, but only for entrepreneurs: This finding supports Lazear's Jack-of-all-Trades theory.
urn:nbn:de:101:1-20080825251
Keywords: J23; 330; (Non-)cognitive abilities; intelligence; earnings; entrepreneur(ship); wage employment; income differentials; Berufswahl; Unternehmer; Arbeitskräfte; Soziale Kompetenz; Kognition; Erwerbsverlauf; Einkommen; USA